Case report: A rare case of central precocious puberty due to hypothalamic hamartoma - Rao, Jayashree Satish; M, Sushmitha; Savitha, M R; Surendra, Thrupthi (Indian Journal of Child Health, 2022)
Precocious puberty defined by the onset of secondary sexual characteristics before 8 years in girls and 9 years in boys. It is more common in females than males and is usually sporadic. Depending on the primary source of hormonal production, precocious puberty is classified as central and peripheral. Precocious puberty in infants is very rare. While investigating a case of precocious puberty, it is essential to progress systematically, with an identification of isolated or complete precocious puberty followed by bone age estimation, relevant hormonal assays, including GnRH stimulation, as well as neuroimaging when indicated. We present a case of isosexual (central) precocious puberty in a 1 year, 3-month-old girl, who was symptomatic for 1 year of age and was diagnosed to have hypothalamic hamartoma after methodical evaluation and responded to treatment with GnRH agonists.